A study on Aromatic Amino acid Auxotrophs of Rhizobium leguminosarum biovar trifolii - Raad Sultan (College of Education for Pure Sciences, 2009)
Abstract Local Rhizobium leguminosarum bv. trifolii isolate was treated with nitrous acid for mutagenesis. Out of 66 auxotrophic mutants, seven aromatic amino acid auxotrophs were isolated. According to their requirements were classified into three auxotrophic mutants which considered as trp- mutants (RH57, RH114 and RH70), one (RH53) for phenyalanine, two (RH61 and RH84) for tyrosine and one (RH99) for all these amino acids. According to biochemical and intermediates accumulation studies tryptophan auxotrophic mutants could classified into two trpE mutants (RH57 and RH114) and one trp auxotroph (RH70), was tryptophan synthase mutant. Normal symbiotic activity as indicated by mean dry shoot weight, was observed in the tryptophan synthase mutant (RH70). The plants inoculated with aro and trpE mutants fixed nitrogen but significantly less than that of the RH49 inoculated plants, whereas the tyrosine and phenylalanine auxotrophic mutants inoculated clover plants were completely ineffective in nitrogen fixation. The clover plant host seems to provide tryptophan but not tyrosine and phenylalanine to bacteroids in nodules.